INVENTARISASI JENIS DAN TINGKAT KESEHATAN POHON PELINDUNG PADA BEBERAPA TAMAN KOTA PALU SULAWESI TENGAH - Sahril M Taher; I Nengah Suwastika; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Research entitled” Inventory species and levels of demage Shade Tree at some Park in Palu Town, Central Sulawesi”, has been conducted from July to August 2015. The research was aimed to inventory of all shade tree species and to determine the levels of damage in four (4) Parks in Palu Town. The data analysis was done on the percentage of wound compact to the diameter of a main trunk and the percentage of the damaged on the trunk the result of the research showed that, there were six (6) species of shade tree belong to five (5) families with individual number seventy four (74) of Trembesi (Samanea saman (Jack.) Merr.), Thirty five (35) of Mahoni (Swetenia mahagoni (L.) Jacq), Twenty eigh (28) of Katapang (Terminalia catappa Linn), six (6) of Banyam (Ficus benjamina Linn), Four (4) of Johar (Senna seamea Lamk), Two (2) of Kayu Jawa (Lannea coromandelica (Houtt.) Merr). The highest percentage of damage on these four (4) ports was found on of Trembesi (Samanea saman (Jacq.) Merr), which grows in GOR City Park. The average of wounded as 2.71 % and the percentage of damage on stems was 20 %.